Physico - Chemical, Sensory, Textural, and Microbiological Quality of Paneer (Indian Cottage Cheese) Marketed in Bengaluru City - Wangdare, Sachin; Jayaraj Rao, K.; Mishra, Diwakar; Datir, Rupesh (Indian Journal of Marketing, 2017)
Paneer has great value in diet because it is a rich source of high quality proteins, fat, and minerals. Paneer has a short life span of 5-7 days at refrigeration storage, but freshness of the product is lost after 3 days. So, the present study was carried out to know the quality of different brands of paneer sold in Bengaluru city. A total of 80 packets of eight different brands were analyzed for their quality. Wide variation in chemical composition like moisture (49% to 64 %), fat (13.5% to 24%), protein (18% to 23 %), and lactose (1.75% to 4.23 %) existed in the samples. Total bacterial count was observed between 25.40 and 41.10 × 104 /gm, yeast and mold count was observed to be 13.75 and 20.90 × 101/gm, coli-form count was 3.95 to 7.65 × 101 /gm, and Staphylococcus aureus count was 1.10 to 2.20 ×101/gm. Instrumental hardness value varied between 27.56 and 62.22 N. About 75% of the brands did not conform to Food Safety and Standards Authority of India Act (FSSAI) labeling requirements. It is said that India is the largest producer of milk in the world, but improvisations like more awareness about FSSAI Act with respect to packaging, labeling, chemical, microbial requirements, etc. have to be brought about. Further, more hygienic environment during the production of paneer by establishing pre-requisite programs like good manufacturing techniques, good hygienic practices, and Hazard Analysis Critical Control Programme have to be created by manufacturers to bring out utmost quality products in the Indian market.